Secret Clique - Replica Replica - "Kaye, Marilyn" (Hodder Children's Books: London, 2000)
Amy Candler's friend, Tasha becomes concerned when Amy starts hanging around with the cool crowd at school. The change in Amy could not have come at a worse time, as students mysteriously disappear and Amy's boyfriend is stalked
Keywords: English Fiction- Children's stories